Meeting foreignness foreign languages and foreign language education as critical and intercultural experiences - Giorgis, Paola, 1960- (Lexington Books, 2018)
The purpose of the book is to highlight the critical and intercultural potential of foreign languages and foreign language education. The book addresses the complexity of the experience of (foreign) languages and offers both theoretical interdisciplinary suggestions and applied examples of activities.